EFEKTIVITAS PEMBELAJARAN MENGGUNAKAN METODE DARING DI SMAN KOTA PARIAMAN - nurul hamini; Syafri Anwar (JURNAL BUANA, 2021)
Abstrak This study aims to find out about (1) the effectiveness of online learning (2) to find out what problems are faced in online learning (3) to find out what solutions can be done in order to overcome online problems in Kota Pariaman. This type of research uses descriptive quantitative research, data collection techniques use observation techniques, interviews, questionnaires and documentation techniques. Then the informants in this study were geography teachers of SMAN Kota Pariaman and also students of SMAN Kota Pariaman. Furthermore, for data analysis techniques used descriptive data analysis techniques and descriptive statistical calculations using percentage descriptive statistics. The results of this study are (1) The effectiveness of online learning at SMAN Kota Pariaman is: Learning using online methods at SMAN Kota Pariaman is still not effective. Because the management of learning during the Covid pandemic was shifted to online learning, teacher and student communication did not go so well, so that students responded and responded to learning using online methods. Student learning activities do not run properly because there is a lack of response and feedback between teachers and students so that student learning outcomes decline. This is what causes the online learning process to be less effective, including in the "Medium" category because there are still factors or obstacles that hinder the learning process to run effectively. (2) The problems faced in online learning at SMAN Kota Pariaman are the strength of the network / signal which is still not stable, the limitations of students in purchasing internet quota, there are still students who do not have smartphones. (3) Solutions that can be done in order to solve online problems at SMAN Kota Pariaman. From the problems faced in learning using online methods, solutions that can be done by students who are constrained because of the internet network and quota or not having a smartphone can take advantage of school facilities so that they can remain active in the learning process. Students who do not have smartphones can also report to the counseling teacher for solutions such as the teacher providing or giving smartphones to students who really do not have smartphones, this can provide support to students so that they can continue to follow the online learning process. Based on the results of research and discussion in this study, it can be concluded that the effectiveness of learning using online methods at SMAN Kota Pariaman, namely 11 respondents (9.82%) in the Very High category, 27 respondents (24.1%) in the High category, 42 respondents (37.5%) were in the Medium category, 28 respondents (25%) had the Low category, and as many as 4 respondents (4%) had the Very Low category. From these data, 42 students have the highest priority frequency with a percentage of 37.5%, namely in the "Medium" category. So that learning using the online method at SMAN Kota Pariaman can be categorized as moderate, it still cannot be said to be effective due to the obstacles encountered during learning using the online method. Keywords: online learning, effectiveness